Colectiva de Escultura. - Lucas, Juan José; Vega, Blanca Garcia (Valladolid : Junta de Castilla y León, 1996)
Sanchez, Ana Cristina Martinez ; González, Carmen Pérez ; Lobo, Estefania Sanz ; Castro, Félix Angulo ; Cidad, Ignacio Vela ; Maroto, Félix Orcajo ; Blanco, Fernando Sánchez ; CaballoTrébol, Ignacio ; Tascón, Isidro Rodriguez ; Paunero, Javier Bravo ; Martin, José Prieto ; López, Juan Manuel Villanueva ; Prieto, Juanelo Bernardo ; Garcia, Julia Sendin ; Sánchez, Julio Mediavilla ; Torre, Maria Dolores Alejandre de la ; Martin, Rafael Guzmán ; Fernández, Silvia del Arco ; Feliz, Teófilo José Llamas
biografie
Colectiva de Escultura, Biblioteca de Castilla y León, Valladolid, 23 mayo - 14 junio 1996 ; Zamora ; Salamanca ; Avila ; Segovia ; Palancia ; Soria ; León, 1996
Spaans
kunstcatalogus